The master plans: what comes next? - Florence Delmotte; Michel Hubert; Francois Tulkens (Brussels Studies)
The master plan was designed in the framework of the 2002 Regional Development Plan (RDP) as the preferred tool for the development of the fourteen “areas of regional interest”. The plan thus made a triple promise: better coordination of public action, effective public/private partnerships (PPPs) and true democratic participation. The tool was implemented for the first time during the last regional legislature, and is evaluated here based on an empirical study of several cases including the emblematic case of the state administrative district, as well as an afternoon meeting to discuss the results. The authors feel that the administrative complexity, the opposing interests of the public and private sectors, and the difficulty to establish true participation on behalf of inhabitants jeopardise the efficiency of a tool which – when all is said and done – is not binding. But they do not confine themselves to this acknowledgment of (partial) failure. Instead of recommending the elimination of this mechanism, they outline proposals to improve it. Although the ‘master plan’ tool is headed in the right direction, it calls for other advancements towards urban management which is more democratic, more effective, respectful of collective interests and beneficial for the future of the city.